2019
DOI: 10.1002/elan.201800865
|View full text |Cite
|
Sign up to set email alerts
|

Facile Non‐enzymatic Lactic Acid Sensor Based on Cobalt Oxide Nanostructures

Abstract: In this study, we have investigated the effect of counter anions on the morphology of cobalt oxide nanostructures. The nanostructures of cobalt oxide are prepared by a low temperature aqueous chemical growth method. The morphology of cobalt oxide nanostructure material was investigated by scanning electron microscopy and the crystalline structure was studied by powder X‐ray diffraction technique. The cobalt oxide nanostructures exhibit the nanowire, lump, bundle of the nanowire and flower‐like morphologies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In the first place, specific features of nanomaterials are exploited to promote lactate oxidation mechanism over other species. For example, Change et al proposed a non-enzymatic lactate sensor by using cobalt oxide nanostructures [ 51 ]. The authors indicated that the material possessed Co 2+ and Co 3+ centres while the material was embedded in solution.…”
Section: Electrochemical (Bio)sensor Transduction Approachesmentioning
confidence: 99%
“…In the first place, specific features of nanomaterials are exploited to promote lactate oxidation mechanism over other species. For example, Change et al proposed a non-enzymatic lactate sensor by using cobalt oxide nanostructures [ 51 ]. The authors indicated that the material possessed Co 2+ and Co 3+ centres while the material was embedded in solution.…”
Section: Electrochemical (Bio)sensor Transduction Approachesmentioning
confidence: 99%
“…The amperometric lactate biosensor detects the current by applying a specific voltage between the working electrode and the reference electrode, and the measured current is proportional to the concentration of analyte in the solution for quantitative analysis [ 21 , 47 ]. Compared with other types of electrochemical biosensors, the amperometric type can simultaneously measure multiple substances and reflect the content of the analyte more intuitively and has the advantage of being disposable.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Since the regulation of human lactate during secreting process keeps its concentration within a small fluctuation range, highly sensitive sensors are required to capture the small physiological related concentration fluctuations [ 20 ]. In order to improve the sensitivity of the sensor, researchers applied metal oxides [ 21 , 22 , 23 , 24 , 25 , 26 ], carbon nanotubes (CNTs) [ 27 ], graphene [ 28 , 29 ], novel two-dimensional materials (e.g., MXene) [ 30 , 31 ]. and porous materials (e.g., MOFs) [ 32 , 33 , 34 ] to various types of lactate biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Among transition metal oxides, nanostructures of Co 3 O 4 have been utilized in the nonenzymatic sensing of different biomolecules due to their catalytic activity in mild conditions. [20][21][22][23][24] For example, Kogularasu et al reported the use of Co 3 O 4 polyhedrons to fabricate nonenzymatic electrochemical sensors for detecting hydrogen peroxide. 20 Zhang and Liu utilized Co 3 O 4 nanosheets for the non-enzymatic detection of glucose.…”
Section: Introductionmentioning
confidence: 99%
“…23 Chang et al evaluated the effect of Co 3 O 4 nanostructures on lactic acid-sensing. 24 However, there is no report on the use of nano-berry shaped Co 3 O 4 nanostructures to detect uric acid.…”
Section: Introductionmentioning
confidence: 99%